1984
DOI: 10.1203/00006450-198409000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Cholestatic Effect of Intraperitoneal Administration of Tryptophan to Suckling Rat Pups

Abstract: SummaryThe potential cholestatic effect of amino acids and metabolites of tryptophan were evaluated by use of seven daily intraperitoneal injections to suckling and weanling rat pups. Of the amino acids present in parenteral nutrition solutions, only tryptophan (given at a dose of 4 mM/kg) produced a significant ( p < 0.01) elevation of serum cholylglycine (12.8 2 1.0 pM/liter) as determined by radioimmunoassay, compared to 4.9 f 0.4 pM/liter in salinetreated control animals. Total serum conjugates of cholic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…12 Other investigators have reported altered hepatic function in rats receiving light-exposed parenteral amino acid solutions&dquo; or light-exposed injections of tryptophan. 22,37 Infusion of amino acid solutions has been associated with hepatic dysfunction in laboratory animals38-42 and the hospitalized patient.1-7,15-lS We recently reported the acute dose-related effects of infusion of amino acid solutions using the isolated rat liver preparation. 23,43 Infusion of a solution containing 3 g of amino acids without added vitamins resulted in a significant decrease in bile flow, which was reversible when the amino acid solution was discontinued after 1 hour.23 Significant increases in biliary secretion of amino acids included in the infused solution, were observed' similar to those seen with infusion of the AAV (-L) solution in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Other investigators have reported altered hepatic function in rats receiving light-exposed parenteral amino acid solutions&dquo; or light-exposed injections of tryptophan. 22,37 Infusion of amino acid solutions has been associated with hepatic dysfunction in laboratory animals38-42 and the hospitalized patient.1-7,15-lS We recently reported the acute dose-related effects of infusion of amino acid solutions using the isolated rat liver preparation. 23,43 Infusion of a solution containing 3 g of amino acids without added vitamins resulted in a significant decrease in bile flow, which was reversible when the amino acid solution was discontinued after 1 hour.23 Significant increases in biliary secretion of amino acids included in the infused solution, were observed' similar to those seen with infusion of the AAV (-L) solution in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Light exposure of amino acids in the presence of photosensitizing vitamins has been shown to result in the formation of toxic products.9n° In particular, riboflavin has been implicated in the photooxidation of the amino acids tryptophan, methionine, histidine, tyrosine, and cysteine. [19][20][21][22] We have previously shown that infusion of light-exposed PN is associated with alterations in hepatobiliary function and histology in rats infused with PN for 5, 7, and 10 days.12-l4 Furthermore, in the isolated perfused rat liver, we have shown that the infusion of amino acid solution alone results in an acute, dose-related, decrease in bile flow that is reversible after 1 hour.23…”
mentioning
confidence: 90%
“…In experimental animal studies, Merritt et al 13 observed a direct cholestatic effect of tryptophan in suckling rat pups, and Belli et al 6 showed decreased bile flow in rats with amino acid imbalance. In our study, the plasma levels of the branchedchain amino acids, arginine and taurine, were higher than the control values (mean Ϯ 2SD), in proportion to the amino acid dosage.…”
Section: Discussionmentioning
confidence: 97%
“…1). Subsequent experiments were done by using 1.5 (0.09%), 3.0 (0.18%), and 6.0 g (0.36%) of amino acid solution during the 60-minute infusion period. Data were analyzed by using a computerized statistical package (Crunch Software Corp, Oakland, CA).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Infusion of taurocholate reduced the magnitude of the decrease in bile flow associated with amino acid infusion but did not prevent it. Infusion of amino acid solutions was associated with the following changes in bile: (1) dose-related increases in total free amino acid concentrations; (2) increased osmolarity; (3) increased glucose concentrations; (4) increased potassium concentrations; (5) decreased chloride concentrations; (6) increased oxygen uptake in livers not perfused with added taurocholate; and (7) increased total bile acid concentrations in livers perfused with added taurocholate. Additional investigations are needed to determine whether these associations are attributable to individual amino acids or the total metabolic load of the amino acids.…”
mentioning
confidence: 96%